Adjustment requirements in the liming and fertilization recommendation system for olive trees (Olea europaea L.) in south Brazil - Bender, Darlize Déglan Borges Beulck; Weber, Mirla Andrade; Vieira, Frederico Costa Beber (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
Rio Grande do Sul (RS) is the largest producer of olives in the country and has potential to produce even more. However, the liming and fertilization recommendation system needs to be adjusted for the local soil and climate conditions. The objective of this study was to perform a survey of the nutritional status of olive orchards in production, representative of the central region of RS, seeking to identify the main aspects that need to be improved in the management of fertility. Soil, leaf and fruit samples were collected in 13 adult orchards located in Caçapava do Sul and Cachoeira do Sul/RS, in the years 2016 and 2017, and were submitted to analysis of N, P, K, B contents and soil acidity parameters. Most of the evaluated soils had a high content of Al exchangeable in the 20-40 cm layer, suggesting the need for deeper incorporation of lime on orchard implantation and/or raising the surface pH to favor depth correction. Most of the orchards had N content in the leaves above the recommended one, which is worrying, since the excess of N in the tissue promotes greater vegetative growth and suppresses the flowering. For P and B, discrepancies between leaf and soil levels suggest that the critical soil level is not adjusted to the climate and soil conditions of the region. B was the most restrictive nutrient to fruit yield in the evaluated orchards